Individual Criminal Responsibility for Incitement to Commit International Crimes through Social Media and Online Platforms: Defining the Thresholds of Causation and Intent - Almoatuz A. Munsoor (Journal of Educational and Human Sciences, 2026)
The exponential growth of social media and online platforms has fundamentally transformed the landscape of international criminal law, particularly concerning incitement to commit international crimes. This research examines the legal frameworks governing individual criminal responsibility for incitement conducted through digital channels, focusing on the critical thresholds of causation and intent required for prosecution. Drawing upon jurisprudence from international criminal tribunals, domestic courts, and emerging legal scholarship, this study analyzes how traditional doctrines of incitement have adapted to address the unique characteristics of digital communication, including virality, anonymity, and transnational reach. The research identifies significant challenges in establishing direct causation between online speech and subsequent international crimes, while also exploring the evidentiary requirements for demonstrating specific intent in the digital context. Through comparative analysis of cases from the International Criminal Tribunal for Rwanda, the International Criminal Court, and national jurisdictions, this paper proposes refined criteria for determining when online content crosses the threshold from protected speech to criminal incitement. The findings reveal that courts increasingly recognize the amplifying power of social media while grappling with questions of intermediary liability, algorithmic amplification, and the temporal distance between incitement and criminal acts. This research contributes to ongoing debates about balancing freedom of expression with the imperative to prevent atrocity crimes in the digital age, offering practical recommendations for prosecutors, judges, and policymakers navigating this complex intersection of technology and international humanitarian law.